The subcellular localization of bHLH transcription factor TCF4 is mediated by multiple nuclear localization and nuclear export signals - Greb-Markiewicz, Beata (Sci Rep, 2019)
Transcription factor 4 (TCF4) is a class I basic helix-loop-helix (bHLH) transcription factor which regulates the neurogenesis and specialization of cells. TCF4 also plays an important role in the development and functioning of the immune system. Additionally, TCF4 regulates the development of Sertoli cells and pontine nucleus neurons, myogenesis, melanogenesis and epithelial-mesenchymal transition. The ability of transcription factors to fulfil their function often depends on their intracellular trafficking between the nucleus and cytoplasm of the cell. The trafficking is regulated by specific sequences, i.e. the nuclear localization signal (NLS) and the nuclear export signal (NES). We performed research on the TCF4 trafficking regulating sequences by mapping and detailed characterization of motifs potentially acting as the NLS or NES. We demonstrate that the bHLH domain of TCF4 contains an NLS that overlaps two NESs. The results of in silico analyses show high conservation of the sequences, especially in the area of the NLS and NESs. This high conservation is not only between mouse and human TCF4, but also between TCF4 and other mammalian E proteins, indicating the importance of these sequences for the functioning of bHLH class I transcription factors.